Development and shelf-life testing of tuna loaf with and wihout potassium sorbate. - Demecillo, Catherine M. (College of Fisheries, University of the Philippines, 1994)
Recognizing the feasibility and potential of different alloy based products, the recommended steps in new product development were followed to create a new flavorful, texturized, value-added "alloy" product. Concepts were generated and subsequently subjected to a series of evaluations and refinement. The most potentially successful concept was singled out for further testing: development of tuna loaf was carried out through product development studies. Sensory attributes such as texture; flavor, odor and color were optimized. Results have shown that by carrying out the recommended procedure in new product development, a concept with high market potential can be picked-out and developed into a new product. Through product optimization, the determined optimum levels and combinations of textural ingredients i.e. flour, water and pork fat, are 10%, 5% and 10% respectively, while the standardized levels of spices are 7.5% sugar, 3% salt and 1.25% black pepper. The product's appearance was enhanced by using 0.8% annato powder, a natural food coloring. Using the standardized formulation, the storage stability of the new product was determined through an actual shelf life-life testing. At a later date, two different concentrations of potassium sorbate (KS) were tested. Changes in odor, flavor, and texture during storage were monitored through sensory evaluation, thiobarbituric acid test (TBA) and moisture content determination. This study found out that tuna loaf samples treated with 0.5% and without KS were still acceptable after 27th day of storage. However, the former gained higher acceptability than the latter. On the other hand, use of KS more than 0.5% would make the product less acceptable.